Multipoint Conjugate Observations of Dayside ULF Waves During an Extended Period of Radial IMF. Issue 11 (13th November 2020) - Shi, X.; Hartinger, M. D.; Baker, J. B. H.; Ruohoniemi, J. M.; Lin, D.; Xu, Z.; Coyle, S.; Kunduri, B. S. R.; Kilcommons, L. M.; Willer, A.
Abstract: Long‐lasting Pc5 ultralow frequency (ULF) waves spanning the dayside and extending from L  ∼ 5.5 into the polar cap region were observed by conjugate ground magnetometers. Observations from MMS satellites in the magnetosphere and magnetometers on the ground confirmed that the ULF waves on closed field lines were due to fundamental toroidal standing Alfvén waves. Monochromatic waves at lower latitudes tended to maximize their power away from noon in both the morning and afternoon sectors, while more broadband waves at higher latitudes tended to have a wave power maximum near noon. The wave power distribution and MMS satellite observations during the magnetopause crossing indicate surface waves on a Kelvin‐Helmholtz (KH) unstable magnetopause coupled with standing Alfvén waves. The more turbulent ion foreshock during an extended period of radial interplanetary magnetic field (IMF) likely plays an important role in providing seed perturbations for the growth of the KH waves. These results indicate that the Pc5 waves observed on closed field lines and on the open field lines of the polar cap were from the same source. Plain Language Summary: The Earth's magnetic field lines can oscillate at ultralow frequencies (ULF: 1 mHz to 5 Hz). These natural oscillations of closed magnetic field lines, analogous to vibrations on a stretched string, are also called geomagnetic pulsations or ULF waves. ULF waves play a key role in the transfer of energy from terrestrial space to Earth's upper atmosphere. In this study, we report a long‐lasting large spatial scale ULF wave event observed by ground observatories from both hemispheres. Together with satellite measurements in space, we are able to confirm that these waves were driven by upstream turbulent structures due to the interaction between matter and electromagnetic fields emitted from the Sun and the Earth's outer atmosphere and magnetic field. Key Points: Pc5 ULF waves were observed across the whole dayside from L  ∼ 5.5 into the polar cap region, in contrast to typical conditions Coordinated space and ground observations indicate that the waves on closed field lines were due to fundamental standing Alfvén waves The ion foreshock during radial IMF conditions provides seed perturbations for the growth of KH waves which generate the dayside ULF waves